Sosialisasi Peduli Lingkungan Dalam Upaya Kelestarian Ekosistem Biota Laut Sebagai Pendukung Pariwisata di Pesisir Desa Wisata Wargasara, Pulau Tunda, Kabupaten Serang, Banten - Mayasari, Ira; Sira, Oktovia Yacomina; Huwaida, Novia Arini (Jurnal Pemberdayaan Pariwisata; Vol 6 No 1 (2024): Jurnal Pemberdayaan Pariwisata, 2024)
The coast of Wargasara Tourism Village is a coral sand beach, has very beautiful marine life and coral reefs and still maintains its authenticity. The increasing tourist activity on the coast of Wargasara Tourism Village poses a threat to the preservation of marine biota and coral reefs. The aim of this activity is to encourage the survival and preservation of marine biota, break waves and prevent coastal erosion. There were 10 socialization participants consisting of 2 groups of coastal and marine park managers, each consisting of 5 people. The method used is socialization and practice regarding coasts and marine parks, a question and answer method to provide feedback to participants. Socialization and practical activities succeeded in increasing environmental awareness and community involvement in environmental conservation of marine biota ecosystems. Socialization and practical activities succeeded in increasing environmental awareness by 70% among participants as measured through questionnaires before and after the activity. The advice given is to increase the number of marine biota seeds to anticipate damage to the underwater ecosystem, carry out checks at least once a month to maintain the underwater ecosystem, and strengthen public awareness about disposing of rubbish . Keywords: biota, marine park, community